Impact of TH‐UWB interference on MB‐OFDM UWB systems: interference modeling and performance analysis. Issue 8 (4th March 2015) - Sarabchi, Farshad; Nerguizian, Chahé
Abstract: In this paper, the coexistence issue between multiband‐orthogonal frequency‐division multiplexing (MB‐OFDM) and time‐hopping ultra‐wideband (TH‐UWB) networks is widely analyzed. For this purpose, to study and model the TH‐UWB interference, an analytical framework which describes key features of the interference distribution is provided. The interference distribution is studied in the context of TH‐UWB's signaling parameters. Our results reveal that the interference distribution highly depends on its time‐hopping parameters. Therefore, choosing proper time‐hopping parameters leads to less destructive interferences. The Generalized Gaussian and the Symmetric‐ α ‐Stable (S α S) distributions are used to model the interference‐plus‐noise signal. The maximum likelihood and a characteristic function‐based regression‐type methods are adopted to estimate parameters of Generalized Gaussian and S α S distributions, respectively. Moreover, the interference channel effects on the impulsive behavior of the TH‐UWB signal is studied. It is shown that impulsive behavior of the faded interference signals highly depends on the channel time‐dispersiveness. Furthermore, an exact performance of a multiband‐orthogonal frequency‐division multiplexing system impaired by a TH‐UWB system is derived. The comparison of the analytical performance, the empirical simulation, and the approximation results show that both approximation methods are valid for low interference‐to‐noise‐ratio, while S α S provides a more accurate approximation for high interference‐to‐noise‐ratio. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : In this research article, the coexistence issue between MB‐OFDM and TH‐UWB networks is widely analyzed. In order to study and model the TH‐UWB interference, an analytical framework which describes key features of the interference distribution is provided. The interference distribution is studied in the context of TH‐UWB's signaling parameters. It is shown that choosing proper time‐hopping parameters leads to less destructive interferences. Moreover, the Generalized Gaussian and the Symmetric‐ α ‐Stable distributions are used to model the interference‐plus‐noise signal. Furthermore, an exact performance of a MB‐OFDM system impaired by a TH‐UWB system is derived.